Dedoping induced interfacial instability of poly(ethylene imine)s treated PEDOT:PSS as low-work-function electrodes - Cai, Wanzhu; Österberg, Thomas; Jafari, Mohammad Javad; Musumeci, Chiara; Wang, Chuanfei; Zuo, Guangzheng; Yi, Xiaolong; Luo, Xuhao; Johansson, Jim; Kemerink, Martijn; Ouyang, Liangqi; Ederth, Thomas; et al. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2019)
Transparent organic electrodes printed from high-conductivity PEDOT: PSS have become essential for upscaling all-carbon based, low-cost optoelectronic devices. In the printing process, low-work-function PEDOT: PSS electrodes (cathode) are achieved by coating an ultra-thin, non-conjugated polyelectrolyte that is rich in amine groups, such as poly (ethylene imine) (PEI) or its ethoxylated derivative (PEIE), onto PEDOT:PSS surfaces. Here we mapped the physical and chemical processes that occur at the interface between thin PEIx (indicating either PEI or PEIE) and PEDOT:PSS during printing. We identify that there is a dedoping effect of PEDOT induced by the PEIx. Using infrared spectroscopy, we found that the amine-rich PEIx can form chemical bonds with the dopant, PSS. At lower PSS concentration, PEIx also shows an electron-transfer effect to the charged PEDOT chain. These interface reactions lock the surface morphology of PEDOT: PSS, preventing the redistribution of PSS, and reduce the work function. Subsequent exposure to oxygen during the device fabrication process, on the other hand, can result in redoping of the low-work-function PEDOT: PSS interface, causing problems for printing reproducible devices at ambient conditions.